2010
DOI: 10.1159/000284398
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 and Interleukin-6 Gene Polymorphisms in Patients with Advanced-Stage Endometriosis

Abstract: Background/Aims: The aim of this study was to investigate the possibility that the K469E and G241R polymorphisms in the intercellular adhesion molecule-1 (ICAM-1) gene and the C-634G polymorphism in the interleukin (IL)-6 gene are associated with endometriosis in the Korean population. Methods: The ICAM-1 gene K469E and G241R polymorphisms and the IL-6 gene C-634G polymorphism were evaluated in 390 patients with endometriosis and 351 controls by polymerase chain reaction-restriction fragment length polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
2
13
0
1
Order By: Relevance
“…For further analysis, 54 full text articles were obtained. After thorough evaluation, 17 studies were found to be repeated in the database (Hsieh et al., ; Wieser et al., , ; Asghar et al., ; Teramoto et al., ; Bhanoori et al., ; Kitawaki et al., ; Zhao et al., ; Chae et al., ; Lee et al., ; Lu et al., ; Hank Juo et al., ; Chae et al., ; Vijaya Lakshmi et al., ; Mao et al., , ), 10 did not provide the raw data of TNF‐α/IL‐6 polymorphism that we needed for statistical analysis, and these studies reported specificity and sensitivity without the exact counts (Teramoto et al., ; Luo & He, ; Zhang et al., ; Chae et al., ; Lu et al., ; Zhang et al., ; Hank Juo et al., ; Zhou et al., ; Zhao et al., ; Kim et al., ), six studies were excluded because of duplication of data (Luo et al., , b; ; Zhou et al., , b; Mao et al., ), one was not a study of the human (Zhen et al., ), and three studies were on Caucasians (Wieser et al., , ; Zhao et al., ). Finally, 17 studies were selected (Hsieh et al., ; Lee et al., ; Asghar et al., ; Bhanoori et al., ; Kitawaki et al., ; Luo et al., ; Wang et al., ; Lee et al., ; Chae et al., ; Che et al., , b; Vijaya Lakshmi et al., ; Zeng et al., ; Mao et al., ; Zeng & Huang, ; Mao et al., ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For further analysis, 54 full text articles were obtained. After thorough evaluation, 17 studies were found to be repeated in the database (Hsieh et al., ; Wieser et al., , ; Asghar et al., ; Teramoto et al., ; Bhanoori et al., ; Kitawaki et al., ; Zhao et al., ; Chae et al., ; Lee et al., ; Lu et al., ; Hank Juo et al., ; Chae et al., ; Vijaya Lakshmi et al., ; Mao et al., , ), 10 did not provide the raw data of TNF‐α/IL‐6 polymorphism that we needed for statistical analysis, and these studies reported specificity and sensitivity without the exact counts (Teramoto et al., ; Luo & He, ; Zhang et al., ; Chae et al., ; Lu et al., ; Zhang et al., ; Hank Juo et al., ; Zhou et al., ; Zhao et al., ; Kim et al., ), six studies were excluded because of duplication of data (Luo et al., , b; ; Zhou et al., , b; Mao et al., ), one was not a study of the human (Zhen et al., ), and three studies were on Caucasians (Wieser et al., , ; Zhao et al., ). Finally, 17 studies were selected (Hsieh et al., ; Lee et al., ; Asghar et al., ; Bhanoori et al., ; Kitawaki et al., ; Luo et al., ; Wang et al., ; Lee et al., ; Chae et al., ; Che et al., , b; Vijaya Lakshmi et al., ; Zeng et al., ; Mao et al., ; Zeng & Huang, ; Mao et al., ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the TNF‐α ‐308A/G polymorphism might not be a useful prognostic biomarker for endometriosis, especially in the Asian population. For the IL‐6 ‐634C/G genotype, no association was found with endometriosis in Asians and the results are supported by Chae et al (), who also found no association of the ‐634C/G gene polymorphism with endometriosis, or with any clinical subgroup of endometriosis. The subgroup of endometriosis stages III–IV cases was considered under the condition that one study (Chae et al., ) selected endometriosis stages III and IV as cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the general definition, we classified patients into different groups according to the heterozygous or homozygous of IL-6 -576 (CC/GG/CG) (Oana et al 2014). Similarly, the ICAM-1 phenotypes were also defined as KK/ EE/KE according to the heterozygotes or homozygotes as described by others (Chae et al 2010;Liou et al 2015).…”
Section: Genotypingmentioning
confidence: 99%